Konsep Alkitab (Ulangan 6:4-9) tentang Pendidikan Agama Kristen Anak - Trivena Andrianikus (LPPM STT Baptis Kalvari, 2021)
The significant role of parents in the spiritual growth of their children has become a pivotal point in Christianity. It is found that parents want their children to experience a good spiritual growth and are supported with Christian Education. Based on literature research, it was found that the Bible concept (Deuteronomy 6: 4-9) concerning Child Christian Education is an important thing. Christian Education is a scientific discipline that presents the Bible as the foundation for Christian Education with the aim of glorifying God's name. The most important component that plays the biggest responsible role in Child Christian Education is family. In the Bible, Shema Israel or Jewish’s statement of faith was the foundation of biblical teaching of children. This text related to the importance of education and also was concerning about Israel’s core believe. Shema, as the Israel’s statement of faith was also set out as a commitment and self-proclamation to the one true God.